KONTRIBUSI POWER OTOT LENGAN BAHU DAN KOORDINASI MATA TANGAN TERHADAP KEMAMPUAN PUKULAN SMASH BULU TANGKIS PADA ATLET PUTRA UMUR 10-15 TAHUN PB. BANK RIAU KEPRI PEKANBARU - Yusrini Putri Saragih; Slamet Slamet; Alimandan Alimandan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Some of the problems that occur between him often experience failure in smash and smash that does not fall on the target or the opponent's weak point. The purpose of this study was to determine the contribution of shoulder arm muscle power to the ability to smash, hand eye coordination to the ability to smash in male athletes aged 10-15 years BP. Bank Riau Kepri Pekanbaru. The population in this study amounted to 12 people who came from PB. Bank Riau Kepri Pekanbaru. The instruments used in this study were the Two Hand Medicine Ball Put test, the silent ball throwing test, and the smash ability test. This type of research is correlation in order to find the level of relationship between these variables. Then the data test using the normality test, normality test data with liliefors test, correlation analysis. Data analysis techniques showed that where rX1Y contributed 28.09%, rX2Y contributed 12.96%, RX1X2Y contributed 31.36%. With this data, there is a contribution between these variables.Key Words: Shoulder Arm Muscle Power, Hand Eye Coordination, Smash Punch Ability